Surface Adsorption of Polyethylene Glycol to Suppress Dendrite Formation on Zinc Anodes in Rechargeable Aqueous Batteries - Mitha, Aly; Yazdi, Alireza Z.; Ahmed, Moin; Chen, Pu (ChemElectroChem, 2018)
Aqueous metal batteries routinely suffer from the dendritic growth at the anode, leading to significant capacity fading and ultimately, battery failure from short‐circuit. Herein, we utilize polyethylene glycol to regulate dendrite growth and improve the long‐term cycling stability of an aqueous rechargeable lithium/zinc battery. PEG200 in the electrolyte decreases the corrosion and chronoamperometric current densities of the zinc electrode up to four‐fold. Batteries with pre‐grown dendrites also perform significantly better when PEG is present in the electrolyte (41.4 mAh g−1 vs. 7.9 mAh g−1 after 1000 cycles). X‐ray diffraction and electron microscopy studies show that dendrites in the PEG‐containing electrolyte have been inhibited, leading to much smaller/smoother surface features than those of the control. The facile preparation process of the aqueous electrolyte combined with low cost and vast performance improvement in batteries of all sizes indicates high upscaling viability. Regulating dendrite formation: polyethylene glycol (PEG) is explored as an electrolyte additive for aqueous metal ion batteries. Dendrite formation is regulated by surface adsorption of PEG on the anode. The battery lifespan is enhanced more than five times by preventing runaway dendrite growth. Longer lifespan and higher reliability increase the candidacy of aqueous lithium batteries for energy storage from renewable sources.